Normative cardiopulmonary exercise data for endurance athletes: the Cardiopulmonary Health and Endurance Exercise Registry (CHEER) - Petek, B. J.; Tso, J. V.; Churchill, T. W.; Guseh, J. S.; Loomer, G.; DiCarli, M.; Lewis, G. D.; Weiner, R. B.; Kim, J. H.; Wasfy, M. M.; Baggish, A. L. (European Journal of Preventive Cardiology, 2021)
Aims: Accurate interpretation of cardiopulmonary exercise testing (CPET) relies on age, gender, and exercise modality-specific reference values. To date, clinically applicable CPET reference values derived from a source population of endurance athletes (EAs) have been lacking. The purpose of this study was to generate CPET reference values for use in the clinical assessment of EA. Methods and Results: Prospective data accrued during the clinical care of healthy EA were used to derive CPET reference values and to develop novel equations for VO2peak. The performance of these equations was compared to the contemporary standard of care equations and assessed in a discrete EA validation cohort. A total of 272 EA (age = 42 ± 15 years, female = 31%, VO2peak = 3.6 ± 0.83 L/min) met inclusion criteria and comprised the derivation cohort. VO2peak prediction equations derived from general population cohorts described a modest amount of VO2peak variability [R2 = 0.58-0.70, root mean square error (RMSE) = 0.46-0.54 L/min] but were mis-calibrated (calibration-in-the-large = 0.45-1.18 L/min) among EA leading to significant VO2peak underestimation. Newly derived, externally validated VO2peak prediction equations for EA that included age, sex, and height for both treadmill (R2 = 0.74, RMSE = 0.42 L/min) and cycle ergometer CPET (Cycle: R2 = 0.69, RMSE = 0.42 L/min) demonstrated improved accuracy. Conclusion: Commonly used VO2peak prediction equations derived from general population cohorts perform poorly among competitive EA. Newly derived CPET reference values including novel VO2peak prediction equations may improve the clinical utility of CPET in this rapidly growing patient population.